Penerapan Model Pembelajaran Project Base Learning pada Materi Tekanan di MTs NW Mamben - Islami, Anggun Variasi; Sunni, M. Abdurrahman (TSAQOFAH, 2021)
This study aims to improve student learning outcomes in MTs. NW Mamben. This research is a classroom action research conducted in two cycles. Each cycle consists of two meetings. The research sample is class VIII even semester students of 2021-2022 MTs NW Mamben. The results showed a significant increase in student learning outcomes, especially in student activities. The students' activities that increased the most were group discussion activities when completing projects and answering questions. This shows that learning with the PBL model has a positive impact on improving student learning outcomes.